Paraurethral Leiomyoma as an Incidental Finding in Patient with Fibroid Uterus - Dmitry Fridman; Marnie Abeshouse; Alexander Sankin (Hindawi Limited, 2018)
Paraurethral leiomyomas are rare benign fibromuscular tumors developing from urethra. The presenting symptoms are usually related to mass effect. We present a case of an incidental diagnosis of a paraurethral leiomyoma in a patient with a fibroid uterus. Case was managed by hysterectomy concurrent with periurethral leiomyoma excision. Patient had uncomplicated clinical course. Due to close localization of paraurethral leiomyoma to urethra and bladder care must be taken to minimize the injury during resection.